The role of structural variations in Alzheimer’s disease and other neurodegenerative diseases - Wang, Hui; Wang, Li-San; Schellenberg, Gerard; Lee, Wan-Ping (Frontiers in Aging Neuroscience, 2023)
Dozens of single nucleotide polymorphisms (SNPs) related to Alzheimer’s disease (AD) have been discovered by large scale genome-wide association studies (GWASs). However, only a small portion of the genetic component of AD can be explained by SNPs observed from GWAS. Structural variation (SV) can be a major contributor to the missing heritability of AD; while SV in AD remains largely unexplored as the accurate detection of SVs from the widely used array-based and short-read technology are still far from perfect. Here, we briefly summarized the strengths and weaknesses of available SV detection methods. We reviewed the current landscape of SV analysis in AD and SVs that have been found associated with AD. Particularly, the importance of currently less explored SVs, including insertions, inversions, short tandem repeats, and transposable elements in neurodegenerative diseases were highlighted.